PEMBUATAN VIRGIN COCONUT OIL (VCO) : PEMECAHAN EMULSI DENGAN METODE ULTRASONIK - Nely Fatwatun R.; Kaunaini Chusna; Bambang Pramudono (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
Coconut tree is one of the strategic commodities which became the pre-eminent national. In addition to being one of the strategic commodities, coconut tree has many benefits start from the root, stem, leaf, fruit, up to they sheath. VCO is one product of the coconut plant has bigger added value and beneficial to health. Research needs to be done to study the manufacture of VCO that is created by using ultrasonic waves and compare it with the existing method of VCO by using secondary data. The purpose of this research was to determine the influence of temperature and ratio of water and coconut in the manufacture of VCO with ultrasonic method, analyze the physical properties chemical VCO and compare the results with SNI, comparing the results of ultrasonic method with VCO created with another method, as well as find out the methods and conditions of operation of VCO with good quality and high yield. Manufacture of VCO is done by the method of ultrasonic wave using time 60 minutes with frequency 70kHz. Changing variables used are coconut water ratio of 1:1; 1,5:1; 2:1 and the temperature is 30OC, 40OC, 50OC. The resulting calculated oil yield and quality are analyzed. Analysis undertaken include organoleptic analysis, moisture content, free fatty acid, peroxide value, number Iod, and Fe contamination. The research results showed that ultrasound can be used to break down the emulsion VCO-water. Ratio of the coconut and water as well as in the manufacture of coconut milk and temperatures when ultrasonic affects yield. physical and chemical properties of two samples VCO with the highest yield has according to SNI. VCO is made by the method of ultrasonic have the lowest yield, but the quality is the best if compared to the method of fermentation, enzimatis, pumping and centrifugation. Ultrasonic methods, variables coconut and water ratio of 2:1 at temperature 30OC is the maximum operating conditions which produced the VCO with good quality and high yield, but ultrasonic method is not a method that can produce the highest yield, despite having the best quality.